IMPLEMENTATION OF ACCRUAL POLICY, INTERNAL CONTROL SYSTEM AND PUBLIC SERVICE INDEX IN CONTROLLING GOVERNMENT FINANCIAL MANAGEMENT - rohman, abdul; Efriandy, Iwan; Khamisah, Nur (Fakultas Ekonomi Universitas IBA, 2024)
The development of the application of accrual accounting has become a global trend but is still not fully embraced by the Indonesian government. The implementation of accrual accounting in government raises many problems. This research is quantitative using the influence test method. The population is the Indonesian government and the sample uses Indonesian regional governments. The aim of this research is to examine whether accrual policies and the maturity of the internal control system and public service index can influence the efficiency of regional government financial control. The results of this research indicate that partially the discretionary accrual variables, both the Jones model approach and the modified Jones model approach, have an effect on the efficiency of local government financial management. Apart from that, the public service index variable also influences the efficiency of local government financial management. Meanwhile, the internal control system maturity variable has no effect on the efficiency of regional government financial control. Simultaneously, the variable discretionary accruals of the Jones model, discretionary accruals of the modified model, and the maturity of the government's internal control system influence the efficiency of financial management. So, to increase the efficiency of financial management, local governments can increase the application of discretionary accruals and pay attention to public services.